Reading modern Southeast Asian art history through exhibitions - Hong, Grace Chu Yu (Nanyang Technological University, 2020)
Exhibitions have been crucial to the construction of modern Southeast Asian art history since the first Southeast Asian art exhibition in 1957. They are a primary means for canon building through tangible displays of artworks and published writings. Established in 2015, the National Gallery Singapore (NGS) has quickly become the most influential institution for producing exhibitions of modern Southeast Asian art. The NGS’s exhibitions have been instrumental in shaping a new master narrative of modern Southeast Asian art history—one that has been posited as originating in nineteenth century colonialism and remains deeply informed by narratives of Western modernism. However, the role of the NGS’s exhibitions in the construction of a modern Southeast Asian art history has yet to be scrutinised beyond the museum’s publicised regional engagement—and in relation to the Singapore’s national agenda. This thesis examines the complexities and tensions of the NGS’s curatorial position through two significant exhibitions: "Between Declarations and Dreams: Art of Southeast Asia Since the 19th Century" (2015–2020), and "Reframing Modernism: Painting from Southeast Asia, Europe and Beyond" (2016). Through the close study of curatorial strategies and exhibition mechanics behind the display of artworks by two major Southeast Asian artists, Nguyen Gia Tri (b. 1908, Vietnam–d.1993, Vietnam) and Cheong Soo Pieng (b. 1917, China–d. 1983, Singapore), this study argues that the NGS’s exhibitions have cultivated a dominant narrative that ultimately suppresses the complexity and diversity of other Southeast Asian countries’ art histories towards the goal of positioning Singapore as the regional centre for Southeast Asia.